I genitori come soggetti epistemici nella relazione con i servizi sociali, sanitari, educativi. Una ricerca basata sulla Teoria dell’Attività - Alga, Maria Livia; Di Masi, Diego; Sità, Chiara (Rivista italiana di educazione familiare, 2025)
Parents who encounter the professional service system risk not being recognized as subjects who construct relevant knowledge for the support process. This leads to a situation of “epistemic injustice,” visible in professional practices entirely unbalanced on the service providers’ expertise and functioning. The research aims to explore the knowledge that parents construct about the service system during their experience as beneficiaries. Using the activity theory framework, the research employed semi-structured interviews to examine how parents position themselves regarding the object, norms, tools, community, and division of labor. The discussion highlights how parents’ knowledge can transform the collective understanding of the situation they inhabit with professionals, thus promoting the development of more informed and participatory courses of action.